Sustainability- A Multiple Regression Model For EU-27 - Adina A. NEAMTU (Communications of International Proceedings, 2021)
Sustainability is a must. The sanitary crisis reminded us all that a sustainable economy is the only way forward. The Green Deal of European Union designs the strategy needed to achieve this goal. Tracking progress, however, is not an easy job as wellbeing a multifaceted concept. The present paper aims to find a correlation between gross domestic product per capita, a metric frequently used for measuring the wellbeing of individuals, GINI Index and Social Progress Index for the 27 Member States. The conclusions are intriguing: countries with highest gross domestic product per capita do not have the best GINI Index, nor the best Social Progress Index.
Keywords: sustainability; Green Deal; wellbeing; income inequality; EU-27.